Respuesta :

Answer:

(1,-1)

Step-by-step explanation:

[tex] \large{ \begin{cases} y = 2x - 3 \\ y = - x \end{cases}}[/tex]

Since both are y-isolated equation. We can combine both.

[tex] \large{2x - 3 = - x}[/tex]

Since we want to solve for x-term, we need to isolate x-term.

So we move from -x which is the right side to x.

[tex] \large{2x - 3 + x = 0} \\ \large{3x - 3 = 0} \\ \large{3x = 3} \\ \large{x = 1}[/tex]

But we are not done yet. Solving system of equations, you must solve for y-term as well. (Because we have to answer in ordered pairs which are (x, y))

Substitute x = 1 in any given equations but I will substitute x = 1 in y = -x

[tex] \large{y = - x} \\ \large{y = - 1}[/tex]

Since we have got y-value. Therefore the answer is (1,-1)